Aportaciones a la Zoogeografía del Hayedo del Moncayo - Longares Aladrén, Luis Alberto; Lozano Valencia, Pedro; Rubio Recio, José Manuel (Geographicalia, 2017)
The paper explains a zoogeographic study in the Moncayo beechwood (Aragón, Spain) in relation with the border tree situation of this vegetal group. Significant fauna presences and absences were detected comparing with other beechwoods which indicate the ecological position and the real corological value of this site.
Keywords: Zoogeography; corology; fauna; beechwood.